First family detail Secret Service agents reveal the hidden lives of the presidents - Kessler, Ronald; Bybee, Michael (Westminster, MD Books on Tape, 2014)
Since publication of his bestselling book In the President's Secret Service, investigative reporter Ronald Kessler has continued to penetrate the wall of secrecy that surrounds the U.S. Secret Service, breaking the story that Secret Service agents who were to protect President Obama hired prostitutes in Cartagena, Colombia and revealing that the Secret Service allowed a third uninvited guest to crash a White House state dinner. Now, Kessler presents far bigger and more consequential stories about our nation's leaders and the agency sworn to protect them. Kessler widens his scope to include presidential candidates and former presidents after they leave the White House. In particular, he focuses on First Ladies, their children, and their relationships with the presidents. From observing reckless behavior that threatens the country's safety, to escorting presidential mistresses, to watching their own agency take risks that could result in an assassination, Secret Service agents know a secret world that Ronald Kessler exposes in breathtaking detail.--From publisher description.
Subtitle from container.
Unabridged.
Compact discs.
Read by Michael Bybee.
101768
Keywords: United States. -- Secret Service -- History; Presidents -- United States -- Family; Presidents' spouses -- Protection -- United States; Children of presidents -- Protection -- United States; Secret service -- United States -- History; Presidents -- Family; Secret service; United States; Audiobooks